Computational model for energy aware TDMA-based MAC protocol for wireless sensor network system - A. Rashid, Rozeha; Ehsan, Wan Mohd. Arif; Zaharim, Azami; Fisal, Norsheila (2007)
The development of wireless sensor networks (WSN) can be motivated by several types of applications such as habitat monitoring, smart health care system, building automation, and etc. These applications however, demand an energy-efficient WSN which can prolong the network lifetime and can provide high throughput, low latency and delay, and high packet received rate data communication. The ability of wireless network structure to maximize network lifetime is among the hot topic due to limitation of resources such as energy, processing and memory, in sensor network architecture itself. This paper proposes a novel approach that tries to reduce idle energy consumption by implementing active-sleep algorithm named energy aware A-MAC protocol. The result from the computational model shows that the algorithm can prolong the network lifetime due to efficiency in energy consumption from time slot management.